2012
DOI: 10.1111/cas.12000
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic smoking and postoperative survival in lymph node‐negative esophagus squamous cell carcinoma patients

Abstract: Smoking is well known as a risk factor for esophageal cancer, but controversial as a prognostic factor. Moreover, evidence is scarce that a dose-response relationship exists. We conducted a retrospective study on the effect and dose-response relationship of prediagnostic smoking on the postoperative disease-specific survival of patients with lymph node-negative esophageal squamous cell carcinoma (ESCC). We enrolled 643 patients with lymph node-negative ESCC who had undergone esophagectomy between 1990 and 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Smoking and alcohol drinking were found to be negative prognostic factors in univariate analysis, but they did not have significant influence on survival in multivariate analysis. Prediagnostic smoking has been reported as an independent prognostic factor for patients with ESCC (21). The impact of alcohol consumption on survival in patients with ESCC was demonstrated by two large cohort studies (22,23).…”
Section: Discussionmentioning
confidence: 97%
“…Smoking and alcohol drinking were found to be negative prognostic factors in univariate analysis, but they did not have significant influence on survival in multivariate analysis. Prediagnostic smoking has been reported as an independent prognostic factor for patients with ESCC (21). The impact of alcohol consumption on survival in patients with ESCC was demonstrated by two large cohort studies (22,23).…”
Section: Discussionmentioning
confidence: 97%
“…in that smoking might alter the behavior of a tumor and promote its progression. [48][49][50] By contrast, the use of surgery alone, trimodality therapy, or definitive CCRT causes side effects in cardiopulmonary functions. However, evidence for prediagnosed alcohol consumption as a prognostic factor in patients with ESCC is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…[45][46][47] Our results are also compatible with those from previous studies. [48][49][50] By contrast, the use of surgery alone, trimodality therapy, or definitive CCRT causes side effects in cardiopulmonary functions. [51][52][53] Patients with ESCC who have alcohol consumption and cigarettes smoking habits may have poor cardiopulmonary function and, accordingly, cannot tolerate aggressive treatments, resulting in more complications with similar treatments.…”
Section: Smoking Causes Genetic or Epigenetic Alterations;mentioning
confidence: 99%
“…Smoking is well known in damaging public health on a global scale by playing an important role in the development of many cancers . Well‐conducted population‐based studies have reported that cigarette smoking would significantly increase the risk of esophageal cancer, and it also associated with worse outcomes . However, the specific molecular targets affected by cigarette‐derived carcinogens have not been thoroughly identified.…”
Section: Introductionmentioning
confidence: 99%